A prospective study of specimen eversion to lateral rectum and valgus resection for low rectal cancer - Qian, Long; Huang, Xiaoxu; Xu, Li; Chen, Hao; Cao, Tingting; Wang, Song; Luo, Can; Xia, Yabin (Frontiers in Surgery, 2022)
Purpose To investigate the safety and efficacy of a reverse puncture device (RPD) and specimen eversion of the rectum for resection in total laparoscopic proctectomy. Methods In a prospective study from August 2019 to March 2021, 40 patients underwent a procedure with an RPD and specimen eversion of the rectum for total laparoscopic low rectal cancer resection, that is natural orifice specimen extraction surgery (NOSES), were included in the NOSES group. Forty patients in the control group underwent conventional laparoscopic radical resection for low rectal cancer and were included in the LAP group. Intraoperative- and postoperative-related indicators, recovery and inflammatory factors, quality of life (QOL) and mental health were compared. Results All operations were successfully completed. Compared with the LAP group, the NOSES group showed better short-term outcomes, such as time to eating, postoperative pain, and especially postoperative incision-related complications. At the same time, postoperative inflammatory factor levels, psychological trauma, life-related anxiety and depression scores, and QOL were better in the NOSES group than in the LAP group. Conclusions The application of an RPD and specimen eversion of the rectum for total laparoscopic low rectal cancer resection is a technically feasible and safe approach with a short-term curative effect.